Effects of applied training loads on the aerobic capacity of young soccer players during a soccer season - Jastrzebski, Z.; Rompa, P.; Szutowicz, M.; Radziminski, L. (The Journal of Strength and Conditioning Research, 2013)
The aim of this study was to examine the effects of applied training loads on the aerobic capacity, speed, power, and speed endurance of young soccer players during 1 soccer season. The participants in the study were 19 young male soccer players (age: 16.61 ± 0.31 years; weight: 64.28 ± 6.42 kg; height: 176.58 ± 5.98 cm). The players completed 150 training sessions and 54 games over the course of 1 soccer season. The training intensity was divided into 4 categories: (a) aerobic performance (61% of the total training duration), (b) mixed aerobic-anaerobic performance (34%), (c) anaerobic lactate performance (3%), and (d) anaerobic nonlactate performance (2%). No significant changes in the VO2max were observed throughout the season. The players' power level and speed endurance increased significantly with the coincident decrements in their 5-m sprint time. The applied training loads, including 1 high-intensity training session of small-sided games performed during a competitive season, did not significantly change the aerobic capacity of the young soccer players. However, the participants did maintain their VO2max at the elite level. The first squad players (FSPs) reached the highest level of aerobic fitness in the middle of the season, whereas substitute players (SPs) at the end of the season. Moreover, the VO2max in FSP was significantly higher (p < 0.003) than in SP in the middle of the season.